Trends in Human Resource Information Systems and their Impact in Practice - Košťálová, Jana; Bednaříková, Marie; Vostřezová, Martina (Ekonóm, 2017)
Information technologies, social media and communication tools are dramatically developing and have a significant impact on the work in the field of human resource management. The authors of the article recapitulate the development of human resource management support in terms of human resource management information systems, present new trends that can be noticed in this area and assess the advantages and disadvantages associated with their use in practice. At present, enterprises do not view manpower only as a source but as capital which contributes to the achievement of corporate objectives. Tools in the form of human resource management information systems have become an integral part of corporate information systems and, in addition to collecting data related to human resource management and analyzing thereof, they deliver many new features to support the demanding job of human resources specialists while helping to increase productivity and develop human capital.
Trendy v oblasti informačních systémů na podporu personálního řízení a jejich dopad v praxi
Keywords: Human resources management; human resource information system; e-human resource management; web 2.0 technologies; social media; e-learning; business intelligence; řízení lidských zdrojů; informační systém na podporu personálního managementu; e-řízení lidských zdrojů; web 2.0 technologie; sociální média; e-learning; business intelligence